2021
DOI: 10.3390/jcm10245748
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin Resistance with Vascular Ageing in a General Caucasian Population: An EVA Study

Abstract: The data on the relationship between insulin resistance and vascular ageing are limited. The aim of this study was to explore the association of different indices of insulin resistance with vascular ageing in an adult Caucasian population without cardiovascular disease. We selected 501 individuals without cardiovascular disease (mean age: 55.9 years, 50.3% women) through random sampling stratified by sex and age. Arterial stiffness was evaluated by measuring the carotid-to-femoral pulse wave velocity (cfPWV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The insulin signaling has effects on metabolic health and can be targeted to improve the insulin sensitivity in T2DM, obesity, and other metabolic diseases. 25 Previous studies have reported that constitutively active HSF1 in pancreatic islets enhances glucose-induced insulin secretion. Therefore, identification of the molecular mechanisms underlying the effects of HSF1 on muscle glucose utilization is of significant interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insulin signaling has effects on metabolic health and can be targeted to improve the insulin sensitivity in T2DM, obesity, and other metabolic diseases. 25 Previous studies have reported that constitutively active HSF1 in pancreatic islets enhances glucose-induced insulin secretion. Therefore, identification of the molecular mechanisms underlying the effects of HSF1 on muscle glucose utilization is of significant interest.…”
Section: Discussionmentioning
confidence: 99%
“…The insulin signaling pathway has beneficial effects on metabolic health and can be targeted to improve the insulin sensitivity in T2DM, obesity, and other metabolic diseases 25 . Previous studies have reported that constitutively active HSF1 in pancreatic islets enhances glucose‐induced insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The carotid stiffness parameters increase is positively correlated with the increase of fasting glucose, insulin, glycated hemoglobin A1c, HOMA-insulin resistance index, waist circumference, triglycerides, and decrease of high-density lipoprotein cholesterol (Gomez-Sanchez et al 2021). A recent study in adult persons without CVD has demonstrated direct association of carotid-femoral pulse wave velocity with HOMA-insulin resistance index and an inverse relationship with telomere length.…”
Section: Discussionmentioning
confidence: 93%
“…Sensitivity analyses were conducted with the standard for arterial stiffness of 1400 cm/s. Additionally, we explored the relationships between TG/HDL-C and TyG with healthy vascular aging (HVA), normal vascular aging (NVA), and early vascular aging (EVA), defined as < baPWV-percentile < 10th, 10th ≤ baPWV-percentile ≤ 90th, and baPWVpercentile > 90th of the population stratified by age and sex [29]. SAS v9.4 was taken for all analyses (SAS Institute Inc., Cary, NC, USA), with a two-sided P value < 0.05 considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%